Perfil do ensino médio privado em Goiânia na última década do século XX - Araújo, Sônia Maria Maranhão de (2004)
This work presents a bibliographical revision and a research of field, on the subject that it concerns to the elitização of education in Brazil, particularly average education, with implications in the demand for superior education, to break in the relations and changes that they sobrevieram with the advent of the neoliberalismo of of the globalization, causing impact in all the sectors of the society, amongst them, the education, in the social context, in such a way of the pupil how much of the professor, standing out, also, the interference of cause and consequência of this relation in the curricular components and the future life of the pupil, or either, in the work market. Analyzing speeches of professors and official documents that base the Education on Brazil, it is observed that this has been calcada in descontextualizadas bases when is mentioned to the social aspect and predominantly of traditionalistic and elitizante base as for the processes of and to the access of the citizen to education and the learning, being visible the relation of causal nexus between the neoliberalismo, the trend to the privatization, the pupil and the society, in this specific aspect. Evidenced this aspect, it is in this diapasão that if bases the present paper.